Multicolor photonic patterns through an intensity-controlled single photopolymerization step. Issue 77 (7th September 2022) - Foelen, Yari; van Gils, Nieké J. M.; Claessen, Mart D. T.; Schenning, Albertus P. H. J.
Abstract : The UV intensity during photopolymerization allows control over the structural color of a cholesteric liquid crystal (CLC) polymer photonic coating in a single step. Abstract : The UV intensity during photopolymerization allows control over the structural color of a cholesteric liquid crystal (CLC) polymer photonic coating in a single step. Simultaneously, the glass transition temperature ( T g ) of the polymer can be tuned by the applied UV intensity. Most likely the low intensity photopolymerization increases the inhibition time, leading to in situ formation of polymer fragments through oxygen inhibition. The formation of polymer fragments changes the matrix during the inhibition time, which results in a color change before the polymer network is formed. Additionally, these fragments inside the network act as a plasticizer, effectively lowering the T g . This method can be combined with temperature responsive properties based on shape memory to fabricate photonic coatings with multiple, responsive colored patterns. The presented work allows for new functionalities in responsive photonic polymers as multiple colors and response temperatures can be incorporated in a single polymerization step.